2018
DOI: 10.31055/1851.2372.v53.n3.21310
|View full text |Cite
|
Sign up to set email alerts
|

Anatomía de los cladodios de Opuntia (Cactaceae) de la provincia de Buenos Aires, Argentina

Abstract: Anatomía de los cladodios de Opuntia (Cactaceae) de la provincia de Buenos Aires, Argentina. El objetivo de este trabajo fue profundizar el conocimiento de la anatomía de los cladodios de nueve especies de Opuntia que crecen en la provincia de Buenos Aires, Argentina. Se hicieron preparaciones con material fresco y ejemplares de herbario siguiendo métodos habituales para microscopía óptica. Se usaron técnicas histoquímicas para identificar almidón, mucílagos y sales de oxalato. Las principales características … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In Figure 1b,e the internal parenchyma of fresh and dehydrated cladodes is observed. This tissue is characterized by the presence of isodiametric cells, which possess thin cell walls made up mainly of cellulose, and whose function is to store water, for this reason, this tissue is also known as aqueous parenchyma or hydrenchyma [49]. Inside the aqueous parenchyma, the presence of spherical and globose structures known as mucilage cells or mucilage-secreting idioblasts, which are characteristic of Opuntia species, can be distinguished (see arrows).…”
Section: Morphology Of Mucilage Extracted From Fresh and Dehydrated Cladodesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 1b,e the internal parenchyma of fresh and dehydrated cladodes is observed. This tissue is characterized by the presence of isodiametric cells, which possess thin cell walls made up mainly of cellulose, and whose function is to store water, for this reason, this tissue is also known as aqueous parenchyma or hydrenchyma [49]. Inside the aqueous parenchyma, the presence of spherical and globose structures known as mucilage cells or mucilage-secreting idioblasts, which are characteristic of Opuntia species, can be distinguished (see arrows).…”
Section: Morphology Of Mucilage Extracted From Fresh and Dehydrated Cladodesmentioning
confidence: 99%
“…The main function of these cells is the retention of water when the plant is exposed to long periods of drought. In addition, these cells are specialized to retain more than 30% of water as a reserve in the parenchyma area [49][50][51][52]. It is worth noting that size of the cells of the internal parenchyma and the mucilage-secreting idioblasts of the dehydrated cladodes (Figure 1e) is smaller than that of the fresh cladodes (Figure 1b).…”
Section: Morphology Of Mucilage Extracted From Fresh and Dehydrated Cladodesmentioning
confidence: 99%
“…This fact would correspond to a particular adaptive strategy for water conservation in xeric environments. It has been reported that substomatal chambers cross only up to the "hypodermis" in species of Cipocereus (Cactaceae) [12] and extend into the first layer of the cortical parenchyma in Opuntia species [22]. The control of guard cell opening and closing, as well as the depth of the substomatal chambers, is of great importance to the efficiency of water use.…”
Section: Discussionmentioning
confidence: 99%
“…However, the separation of microfossils was good and the abundance of prickly pear phytoliths is obvious. An interesting detail of the cactus tissue is the presence of wide-band tracheids, typical of cactus xylem (Bobich and Nobel 2001;Perrotta and Arambarri 2018). Ring tracheids are found in the xylem cells of a great variety of vascular plants.…”
Section: Bighorn Cave Arizonamentioning
confidence: 99%